Calcifying cystic odontogenic tumor associated with an odontome – a diverse lesion encountered - Radheshyam, Chourasia (Clin Cosmet Investig Dent, 2015)
The human jaw is an exclusive habitat for odontogenic lesions. Ghost cells associated odontogenic lesions are a diverse group with a variety of presentations in the jaws. Calcifying cystic odontogenic tumor is a benign cystic neoplasm of odontogenic origin which demonstrates ghost cells in the epithelial component. This tumor sometimes mimics the features of a cyst clinically and radiographically, but histopathologically as well as behavior-wise shows the features of a tumor. Many classification systems have been proposed and revised from time to time. Presently a dualistic concept is highlighted to classify this group of lesions. The present case highlights a case of calcifying cystic odontogenic tumor associated with a complex composite odontome, which appeared like a cyst clinically and radiographically.